Plato’ Ethics: Semantic Premises - Silva Santos, Bento (Anales del Seminario de Historia de la Filosofía, 2007)
The article examines some Greek terms in relation to the moral values of ancient Greece. The ethical tradition, generally composed of authors who were not exactly professional philosophers, supplied basic and abundant material for the elaboration of platonic ethics. When dealing with the ancient ethics, it is essential to determine the value and the semantic complexity of the more important values (“competitive” and “collaborative” or “peaceful”) together with the respective implications: the axiologic terms have deeply diverse criteria of application, and the criteria of application of the most important terms reflect beyond doubt and, at the same time, reveal the conception of life of the society in its totality and, therefore, the visions concerning the notion of happiness and good life.